Introduction to the Dicke Model: From Equilibrium to Nonequilibrium, and Vice Versa (Adv. Quantum Technol. 1‐2/2019). Issue 1 (13th February 2019) - Kirton, Peter; Roses, Mor M.; Keeling, Jonathan; Dalla Torre, Emanuele G.
Abstract : The Dicke model is a fundamental model of quantum optics that describes the coupling between many two level systems and a single cavity model. One of the key features of the model is a phase transition between a normal phase, in which the atoms are mostly unexcited, and a superradiant phase, in which the atoms emit light coherently into the cavity. For further information see the Progress Report by Emanuele G. Dalla Torre and co‐workers, article number1800043 . (Cover image design: Mor M. Roses.)